Bentuk, Gaya, dan Makna Akting dalam Film Opera Jawa Sutradara Garin Nugroho - Wahyu Novianto (Institut Seni Indonesia Yogyakarta, 2010)
The Forms, Style, and Meanings of Acting in Opera Jawa. This research is qualitative research that intends to understand the structure and form. And action style, and also the meaning of action as a system of sign in a motion picture entitled ‘Opera Jawa’. The answers to the three issues above are found by employing the approach of form and acting style and also theatre semiotics. Theatre semiotics is used to examine the meaning of the acting sign system which is held by the protagonist and antagonist figure. The theatre semiotics approach used is the version of Tedeuksz Kowzan. Kowzan divides the segmentation of the theatre sign system into 13, but this research only focuses on 8 of it. The results of this study are first, the theme of Opera Jawa is violence; second, the protagonist and antagonist characters are always in a paradoxical relationship; third, the plot consists of three round structures. The acting in Opera Jawa is in form of opera acting. It is a transformation form from the realist acting to the symbolic one. Opera Jawa functions as the life guidance to appreciate, respect, and tolerate others. Keywords: Acting, semiotics, form, style, Javanese opera